Organizational culture of Colegio ng Lungsod ng Batangas: npiut to institutional policies - Rose Mae Ann Lumanglas (Universidade Estadual de Alagoas, 2024)
This study aimed to identify current organizational culture in Colegio ng Lungsod ng Batangas so that congruent institutional policies may be developed. Using Cameron and Quinn (2011) Organizational Culture Assessment Instrument (OCAI), the dominant culture was determined. The study adopted descriptive design with a statistical sample of 55 employees on the College. It was found out that the dominant culture of the institution is the Clan Culture which is characterized by values flexibility and internal control. It is an employee-focused culture driven by collaboration, support, and trust. The Adhocracy culture is the least manifested culture, which is characterized by innovation, adaptive and flexible. The study found no significant difference on profile variables with Hierarchy and Market Culture. Conversely, Clan Culture and Adhocracy Culture was found significantly different in terms of gender and age, respectively. The findings and recommendations of this study may be used as a basis when revisiting the college's institutional policies.